Translation Technique Of The Book â€œResep Masakan Indonesia Di 5 Benuaâ€ - Pratama, Agus Darma Yoga; Kardana, I Nyoman (Center of Language and Cultural Studies [CLCS], 2024)
This research investigates the translation strategies in the bilingual cookbook